THE CONJUGACY OF THE ARCTIC COVER AND THE YIELD OF GENERATIONS OF PACIFIC HERRING IN THE NORTHERN PART OF THE SEA OF OKHOTSK (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Based on the materials of MagadanNIRO for 1974–2020, the yield of North Okhotsk herring is considered, depending on the ice conditions. It is shown that the yield of herring generations in the Northern part of the Sea of Okhotsk before 2002 was probably inversely related to the total ice cover of this area in the year of generation. In the subsequent period, this relationship seems to have changed and no longer shows a stable dependence, which is associated with the possible influence of regional responses of the above-mentioned populations and the Sea of Okhotsk ecosystem to the manifestation of climate change. The paper proposes the creation and testing of a new "ice melting index" as well as an index characterizing the ice conditions in the Northeastern part of the Sea of Okhotsk.
Keywords: Sea of Okhotsk; herring; generations; arctic; yield; conjugacy